Exploring the progression of local transparency considering institutional and geographical factors: A latent growth model - Brás, G.; Dowley, K. M.; Marôco, J. (Public Integrity, 2025)
Transparency plays a pivotal role in local governance for various well-documented reasons. This study examines the evolution of local government transparency in Portuguese municipalities during the period Transparency International’s Municipal Transparency Index was operational. We apply latent growth models spanning from 2013 to 2017 which demonstrated that local transparency increased during the analysis period due to institutional isomorphism (normative and mimetic), though we observed asymmetric growth in local transparency across the Portuguese territory. Since this time, municipalities have expanded their responsibilities under Law No. 50/2018, but the MTI is currently unfunded. Given this context, the urgent need to prioritize local transparency is clear, and we propose recommendations for policymakers to conduct an updated assessment. These recommendations take into account regional variations in local transparency and the increasing responsibility of local government transparency efforts to national efforts to achieve the UN Sustainable Development Goals.